Analisis Buku Teks Hadis-Ilmu Hadis Kurikulum 2013 Kelas XII Madrasah Aliyah Peminatan Ilmu-Ilmu Keagamaan - Hidayat, Taufiq (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
This research is a library research (library research). The data analysis technique used is content analysis or document analysis. The document referred to in this study is the Hadith and Hadith Textbook Curriculum 2013 for Class XII. The approach used in this study is the simultaneous hadith research approach. Whereas in fiqh al-hadith uses the approach of fiqh al-hadith al-mawdu’i (thematcic hadith). The primary data source in this research is the Hadith and Hadith Textbook Curriculum 2013 for class XII of Madrasah Aliyah specialization in religious sciences. While the secondary data sources in the form of mutun, mustalah and fiqh al-hadith books and other books that are relevant to research. This study produces conclusions: First, the analysis of the quality of the hadith concluded that the hadith is hasan gharih. Secondly, the analysis of the understanding of hadith concludes that the traditions which are the subject of learning, their understanding is in accordance with their respective themes except for one tradition about a simple lifestyle that feels a little less in accordance with the theme.